A laboration study on behaviour of single pile in vibrated marine residual soil / Raymi Arip - Arip, Raymi (Faculty of Civil Engineering, 2007)
From previous experience of strong earthquake, pile foundation usually failed under liquefaction especially in the soft soil area. Thus, there is a need to study the pile and soil behaviour under vibration. The laboratory study on Prai soft soil will be conducted using vibrating table test. A transparent container 450x300x250 mm and a hollow circular tubing of 20 mm diameter were used in this laboratory. This report focused on observing the soil settlement, displacement and pile behaviour under strong shaking, within 1 translational direction. Settlement, displacement and boiling behaviour were observed and conclusions were made based on the test result obtained.